Authenticity and commercialization. Cambodian theatre in a postcolonial perspective - Delimata, Maria (Journal of Education Culture and Society, 2020)
The article discusses the problem of authenticity and commercialization in the context of the postcolonial theatre in Cambodia. It seems that contemporary art in this country depends on foreign funds and at the same time on the special taste of – mainly – Western donors. The author tries to show, that the epithet “pure Cambodian” is very often used to make art more interesting to tourists. A similar situation can be seen in the crucifixions in Cutud (which annually takes place in a Philippine province – Pampanga with a wide touristic audience) and in Balinese theatre (another good example of a postcolonial, hybrid identity). Moreover, a discourse of the battle between “traditional” and “touristic” points of view does not have one answer. The search for purity can be a cause of petrifying traditional forms, as well as a sign of neocolonialism and (self-)orientalisation. On the other hand, a dialogue between indigenous artists and the others, tourists, may give the art a new profile and new meaning.